EFFICIENCY OF TIME SYNCHRONIZATION METHODS FOR DISTRIBUTED SIMULATION SIMULATION - Krasovska, E. V. (Problems of Informatization and Management, 2005)
This paper is devoted to the problem of estimating the efficiency of time synchronization (AS) algorithms for distributed simulation (RIM). Simulation models consisting of processes that interact through messaging are considered.